Inventory of ethical problems in mobile pre-hospital care - Simone da Silva Oliveira; Mariana Oliveira Antunes Ferraz; Darci de Oliveira Santa Rosa; Kátia Santana Freitas; Elaine de Oliveira Souza; Deisy Vital dos Santos; Marisa Aparecida Amaro Malvestio (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to construct and validate the content of an inventory of ethical problems experienced by nurses in mobile pre-hospital care. Method: a psychometric approach study, developed with the following stages: (1) instrument construction through a theoretical matrix based on deliberative bioethics, scoping review and online qualitative research; (2) content validity by judges; (3) pre-testing with Mobile Emergency Care Service nurses in various Brazilian states. For content validity analysis, the Content Validity Ratio was calculated (CVR>0.45 for judges and CVR>0.35 for the target population). Results: the instrument had 44 items, distributed across four dimensions. Final considerations: the constructed instrument presented sources of evidence of content validity, providing good psychometric measurements and constituting a useful tool for nurses’ practice in the pre-hospital setting.